Buoyancy Effect on a Micropolar Fluid Flow Past a Vertical Riga Surface Comprising Water-Based SWCNT–MWCNT Hybrid Nanofluid Subject to Partially Slipped and Thermal Stratification: Cattaneo–Christov Model - Mohammed Alshehri, Ahmed; Huseyin Coban, Hasan; Ahmad, Shafiq; Khan, Umair; Alghamdi, Wajdi Mohamad (Mathematical problems in engineering, 2021)
This paper provides a comprehensive analysis of the mixed convective flow that comprises SWCNT-MWCNT/water hybrid nanofluid containing micropolar fluid through a partially slipped vertical Riga surface. A Cattaneo–Christov heat flux model is used to examine the heat transport rate. The energy equation is gaining more significance with the effect of viscous dissipation and thermal stratification. The flow model is transformed by convenient transformation into nondimensionless form. The numerical results of nonlinear complex equations are collected using the bvp4c built-in function from MATLAB which is based on the finite difference method. The graphical results are obtained for both hybrid nanofluid and simple nanofluid. The temperature distribution for hybrid nanofluid is higher than that for simple nanofluid when the solid volume fraction increases. The axial friction factor increases with solid volume fraction, porosity parameter, and mixed convection parameter. The velocity graph varies inversely with nanofluid volume fraction and micropolar parameter.